Blood transfusion requirement during caesarean delivery: risk factors (2015)
Background: Group specific blood is often cross-matched ready for all patients scheduled for caesarean section in anticipation of haemorrhage during the surgery. This study was conducted to determine the risk factors for blood transfusion during anaesthesia for caesarean section. Methods: This was a prospective cross-sectional study. A total of 706 pregnant patients scheduled for emergency or elective Caesarean section at the University College Hospital, Ibadan, Nigeria between March and August 2011 were recruited. Participants were followed-up from the date of delivery till the end point of the study which could fall into either of the following conditions: satisfactory postoperative clinical status up to 48 hours post-delivery or death. Transfusion rate was determined and Chi-square test was used to determine if there exist an association between blood transfusion status and preoperative haematocrit level, years of experience of obstetrician, indication for Caesarean Section(CS), CS type (primary or repeat) and HIV status. Results: Transfusion rate was 9.1 %; variables found to be significantly associated with blood transfusion were; preoperative haematocrit less than 26%, increasing parity, years of experience of resident obstetrician, indication for CS (bleeding or not bleeding) and estimated blood loss. Being HIV positive does not increase the need for blood transfusion. Conclusion: Preoperative anaemia, increasing parity and severe blood loss at surgery significantly contribute to the requirement for blood transfusion in patients undergoing caesarean section.